Converting thermal energy to electricity using nanomaterials - Xu, Vivian Wei. (2009)
Thermionic electron emission is a key phenomenon utilized in a variety of applications, from display communications, space propulsion to direct energy conversion. Thermionic converters are an interesting option for lightweight and long-life power generators due to a number of compelling advantages, including all solid construction, no moving parts, and waste heat rejection at high temperature. New class of very high temperature compatible materials, like Carbon nanotubes (CNTs) are currently being investigated for their performance as thermionic emitter cathodes for possible thermionic applications due to their long life time, their ability to be produced in aligned arrays, and their nanoscale tip geometry based on their diameter.